2018
DOI: 10.12688/wellcomeopenres.14683.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-intensity versus low-intensity praziquantel treatment on HIV disease progression in HIV and Schistosoma mansoni co-infected patients: a randomised controlled trial

Abstract: Background: It has been hypothesised that Schistosoma co-infection exacerbates HIV progression, and hence anthelminthic intervention in co-infected individuals will delay it. We evaluated effects of high-intensity versus low-intensity praziquantel treatment of schistosomiasis on HIV disease progression among co-infected patients from fishing populations around Lake Victoria, Uganda. Methods: Between August 2012 and September 2015, we conducted an open-label randomised, controlled trial. Adults, antiretroviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The FF study population included individuals from 10 FF communities [13,19,[37][38][39] as shown in Figure 1. Individuals were approached in community health facilities (CHF) or during voluntary counselling and testing (VCT) campaigns, and were eligible to participate if they had an HIV-1 positive status and were at least 18 years old (FF communities 1-8) or 14 years (FF communities 9-10).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The FF study population included individuals from 10 FF communities [13,19,[37][38][39] as shown in Figure 1. Individuals were approached in community health facilities (CHF) or during voluntary counselling and testing (VCT) campaigns, and were eligible to participate if they had an HIV-1 positive status and were at least 18 years old (FF communities 1-8) or 14 years (FF communities 9-10).…”
Section: Study Design and Populationmentioning
confidence: 99%